Design and Analysis of Mail Management Information System using PIECES Method : A Case Study at Faculty of Mathematics and Natural Sciences of Udayana University - Pasek Agus Ariawan; Indra Sukadiana Putra; Putu Arya Mertasana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Abstract— Information is needed by agencies, companies, organizations, institutions and the environment having no access to the system. Mail is an important means of communication for agencies. The faster the distribution of the mail the faster the information can be obtained by people or agencies. The increasing number of incoming and outgoing mail gives rise to some problems in mail management. From review of some researches, it can be said that the information management system can help handle the problem faced in mail data processing, mail filing, and mail searching. However, there are some drawbacks in the researches, among others the researches reviewed do not explain how the system works in the mail distribution, verification, signing, classification, and prioritization. This research aims to analyze and design an information system of incoming and outgoing mail management using the PIECES analysis. The advantages of the system are among others, it can help computerize data; the process of mail distribution can be real time with mail notification; the incoming mail data can be classified using the classification method; outgoing mail can be made using the SPK method and the mail signing can be made using the barcode system. Index Terms— information system design, mail, PIECES analysis.